Problems and Strategies for Developing Sharia Fintech in Indonesia: Regulatory, Operational, Technology, Financing, and Human Resources Perspectives - Siswadi Siswadi (Smart Society, 2025)
The development of financial technology (fintech) in Indonesia has increased significantly over the past two decades, expanding access to digital financial services, including payments, financing, and investment. Amid this trend, Islamic fintech has emerged as an alternative that operates in accordance with Sharia principles, such as the prohibition of riba (interest), gharar (uncertainty), and maisir (gambling). However, its implementation continues to face challenges in regulatory, operational, technological, financial, and human resource aspects. This study aims to identify the main problems facing Islamic fintech in Indonesia and to formulate development strategies from regulatory, operational, technological, financial, and human resource perspectives. This research adopts a qualitative approach with a case study design. Data were collected through in-depth interviews with informants, including industry practitioners, regulators, and academics, focus group discussions (FGDs), document analysis, and field observations. Semi-structured interviews were conducted to obtain in-depth insights. Data analysis employed thematic analysis and content analysis, with triangulation used to ensure the credibility of the findings. The results reveal several key issues, including the absence of optimal and specific regulations for Islamic fintech, low levels of digital Islamic financial literacy, limited technology-based supervision, and challenges in integrating technology with the existing Islamic financial ecosystem. Financial challenges are also prominent, particularly the risk of default in Sharia-compliant peer-to-peer (P2P) lending services and limited funding sources. The implications of this study highlight the importance of strengthening regulatory frameworks, enhancing Islamic financial literacy, utilizing big data and artificial intelligence for Sharia-compliant credit scoring, and developing integrated human resources to strengthen the inclusion and competitiveness of Islamic fintech in Indonesia.